2018
DOI: 10.1371/journal.pone.0206221
|View full text |Cite
|
Sign up to set email alerts
|

Ascophyllum nodosum extract mitigates salinity stress in Arabidopsis thaliana by modulating the expression of miRNA involved in stress tolerance and nutrient acquisition

Abstract: Ascophyllum nodosum extract (ANE) contains bioactive compounds that improve the growth of Arabidopsis in experimentally-induced saline conditions; however, the molecular mechanisms through which ANE elicits tolerance to salinity remain largely unexplored. Micro RNAs (miRNAs) are key regulators of gene expression, playing crucial roles in plant growth, development, and stress tolerance. Next generation sequencing of miRNAs from leaves of control Arabidopsis and from plants subjected to three treatments (ANE, Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(62 citation statements)
references
References 86 publications
1
61
0
Order By: Relevance
“…Similarly, the high expression of at-miR827 in the presence of NaCl was reduced by the ANE treatment, also increasing the expression of its target AtNLA gene under these circumstances. These studies demonstrated that the alleviation of salt stress when different ANEs are applied results from the contribution of a multitude of different stress-related genes (Jithesh et al 2018) and involves phosphate homeostasis (Shukla et al 2018).…”
Section: Molecular Analysis Of Ane-induced Salinity Stress Tolerance mentioning
confidence: 98%
See 1 more Smart Citation
“…Similarly, the high expression of at-miR827 in the presence of NaCl was reduced by the ANE treatment, also increasing the expression of its target AtNLA gene under these circumstances. These studies demonstrated that the alleviation of salt stress when different ANEs are applied results from the contribution of a multitude of different stress-related genes (Jithesh et al 2018) and involves phosphate homeostasis (Shukla et al 2018).…”
Section: Molecular Analysis Of Ane-induced Salinity Stress Tolerance mentioning
confidence: 98%
“…The putative role of micro RNAs (miRNAs) in the regulation of ANE-triggered changes during salinity stress has also been studied (Shukla et al 2018). miRNAs silence genes postranscriptionally by targeting mRNA degradation or by interfering with translation and their expression is often induced by various abiotic stresses (Shriram et al 2016).…”
Section: Molecular Analysis Of Ane-induced Salinity Stress Tolerance mentioning
confidence: 99%
“…Similar to miR169, miR827 was detected at high abundance across the entire duration of salt stress (sustained; transgressive) only in FL510. The miR827 plays a role in the regulation of responses to phosphate starvation especially under salinity and drought (Lin et al, 2010;Kant et al, 2011;Ferdous et al, 2017;Shukla et al, 2018). The targets of miR827 showed a unique expression in FL510 ( Figure 9C).…”
Section: Mirna Signatures Associated With Transgressive Salt Tolerancementioning
confidence: 99%
“…Pea plants were spray treated with ANE -0.015% (Acadian Seaplants Limited, chemical composition of ANE was reported earlier [44]) and chitosan (CHT) -100 ppm (Sigma Aldrich®), individually and in combination. Plant was sprayed until drip.…”
Section: Treatments and Inoculation Of Pathogenmentioning
confidence: 99%